The importance of physical activity participation among persons with disabilities - Abdullah, Nagoor Meera; Abidin, Noorasiah Zainal; Rahim, Mohamad Rahizam Abdul; Rahman, Zarizi Abd; Gazali, Novri (Edu Sportivo: Indonesian Journal of Physical Education, 2022)
Participation in physical activity and sports is beneficial for psychosocial health among children and adolescents with a disability. People with disabilities are far less likely to engage in physically active lifestyles than are people without disabilities. This study was conducted to investigate the importance of physical activity participation for persons with disabilities. A total of 100 (men = 59, women = 41) persons with disabilities aged between 10 to 40 years old participated in the study. The instrument used was The Benefits of Exercise towards Persons with Disabilities and Social Support to Exercise for Persons with Disabilities developed by Rauzon designed to investigate the importance of physical activity for disabled persons. The research instrument used for this study was a questionnaire on demographics, the benefits of exercise and social support for exercise. Overall, both men and women agreed with five main statements regarding the benefits of exercise: that they can improve blood pressure and cholesterol levels, help to avoid disease, give more energy, help to relieve tension and to have a more positive outlook on life. There is no significant relationship between family support and physical activity participation. However, for social support, there is a significant relationship between friend support and physical activity participation. The most selected statements for social support for both men and women such as offer to exercise with them, complain about the time they spend for exercise, fun exercise, rewards and help to plan activities around their exercise. Physical activity participation for persons with abilities appears to have many benefits, and this knowledge should be shared not only among the disabled but also the non-disabled as it will help them to become better caregivers who will encourage and support the disabled in physical activities. For a deeper insight, further research with more variables is recommended.